Complete Testicular Feminization Syndrome.: Four Cases - Fernández, Miguel A; Schneeberger, Federico; Quadrelli, Roberto; Vaglio, Alicia; Taddeo, Antonio; Banizzi, Sonia; Manzano, Orlando; Benquet, Gabriel (Cirugía del Uruguay, 1980)
Report of fo'ur cases of Complete Testicular Feminization Syndrome, comprising review and classification 30 of disease. The relationship between this type of patient and the surgeon is discussed, with stress on the need for a multidisciplinary approach to treatment. Finall'y and in view of the limited experience on the subject, two criteria are suggested.